Open reduction in neglected elbow dislocation in children: a case series - Irianto, Komang Agung; Parung, Raymond; Sukmajaya, William Putera (Universa Medicina, 2019)
BackgroundElbow deformity in children due to neglected proper fracture management is a devastating condition. The stiffness and pain complicated the function in daily activity. Successful management of neglected elbow dislocation is a challenging problem for orthopedic surgeons. In this study, we aimed to evaluate results of open reduction for neglected elbow dislocation in children.Case DescriptionThis is a case series of 13-14 years old neglected elbow dislocations, for up to 15 months. Open reduction after external distractor and followed by intensive rehabilitation was implemented. Clinical and functional outcome were evaluated within 4-7 years. Initial average elbow flexion was 53,3°, extension was 0°, arc of flexion was 53,3°, arc of pronation-supination was 150° and Mayo Elbow Performance Index (MEPI) was 80. Clinical and functional outcome were evaluated within 4-7 years. At follow-up after open reduction, the improvement in whole range of movement was significant. Average elbow flexion was 118,3°, extension was 36,67°, arc of flexion was 81,67°, arc of pronation-supination was 133°. The average improvement of flexion was 65°, arc of flexion was 31,67°, and arc of pronation-supination was 8,3°. The average loss of flexion was 15,5%, arc of flexion was 44,2%, and arc of pronation-supination was 10,7% compared with uninjured side. The average Mayo Elbow Performance Index (MEPI) was 96,67; all with excellent results.ConclusionPlanned and well execution open reduction in pediatric neglected elbow dislocation may bring back the painless movement within normal daily function.